Chemical composition and metabolizable energy for poultry feeds - Brum, Paulo Antonio Rabenschlag de; Zanotto, Dirceu Luiz; Lima, Gustavo Júlio Mello Monteiro de; Viola, Eduardo Spillari (Pesquisa Agropecuaria Brasileira, 2000)
The values of chemical composition and of apparent metabolizable energy corrected for nitrogen excretion (AMEn) of 11 ingredients used for feeding poultry were determined. The AMEn was determined through two biological essays with broilers from 15 to 23 days of age, housed in metabolic metal cage decks. The total excreta collection method was used. The experimental design was in totally randomized blocks, with seven and six treatments in essays one and two, respectively. Eight replications of ten birds (five males and five females) were used for treatments, in each essay. Experimental diets were composed of 60% of a reference diet with 22% of crude protein and 3,100 kcal kg-1 of metabolizable energy and 40% of the ingredient tested. The experimental period was of four days of adaptation and five days of excreta collection. Values of chemical composition and AMEn determined in this study showed important differences from those reported under Brazilian conditions and abroad. Knowledge of the chemical composition and of the AMEn of the Brazilian ingredients will make possible to formulate more precise ratios for feeding poultry.